The Effect of STEAM-Based Project-Based Learning Model on the Critical Thinking Skills of Eleventh-Grade Students in the Topics of Elasticity and Hooke's Law - Hasani, Riadhatul; 'Ardhuha, Jannatin; Harjono, Ahmad; Kosim, Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
The critical thinking skills must be possessed by students in order to face various problems. To enhance students' critical thinking abilities, a teaching model that can support these skills is needed. This study aims to examine the effect of the Project-Based Learning (PBL) model based on STEAM on students' physics critical thinking skills. The material used in this study is elasticity. This study explores the impact of the Project-Based Learning model as an independent variable on critical thinking skills as a dependent variable. The research method used is a quasi-experimental design with a non-equivalent control group design. The population of this study consists of all 159 students of class XI MIPA at MAN 1 Lombok Tengah. The sample used in this study includes class XI MIPA 5 as the experimental class and class XI MIPA 6 as the control class, selected using purposive sampling technique. Data analysis in this study was conducted using normality tests, homogeneity tests, and hypothesis testing. Based on the data analysis, the final results show that the average critical thinking score for the experimental class was 82.71, categorized as high, and for the control class was 72.96, categorized as medium. The research hypothesis was analyzed using the t-test for pooled variances. The obtained t-value was 5.54, and the t-table value was 1.706 at a 5% significance level. Therefore, since the t-value > t-table, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Based on the analysis results, it can be concluded that there is an effect of the Project-Based Learning model on students' physics critical thinking skills.